Cyclic behavior and failure mechanism of self‐centering energy dissipation braces with pre‐pressed combination disc springs - Xu, Long‐He; Fan, Xiao‐Wei; Li, Zhong‐Xian (Earthquake engineering & structural dynamics, 2017)
Summary A new type of bracing system composed of friction energy dissipation devices for energy dissipation, pre‐pressed combination disc springs for self‐centering and tube members as guiding elements is developed and experimentally studied in this paper. The mechanics of this system are explained, the equations governing its hysteretic responses are outlined and large‐scale validation tests of two braces with different types of disc springs are conducted under the condition of low cyclic reversed loading. The experimental results demonstrate that the proposed bracing system exhibits a stable and repeatable flag‐shaped hysteretic response with an excellent self‐centering capability and effective energy dissipation throughout the loading protocol. Furthermore, the maximum bearing force and stiffness are predicted well by the equations governing its mechanical behavior. Fatigue and destructive test results demonstrate that the proposed bracing system can maintain stable energy dissipation and self‐centering capabilities under large deformation cyclic loading even when the tube members exceed the elastic limit and that a larger bearing capacity is achieved by the system that has disc springs without a bearing surface. Copyright © 2016 John Wiley & Sons, Ltd.